Combatendo a "corrupção" em Cascavel: análise de processos da Comissão Geral de Investigações em 1969 e 1970 - Krüger, Paulo Roberto (2015)
This dissertation focus on the analysis of CGI s (General Commission of Investigations) processes, in the city of Cascavel-PR, which occured in 1969 and 1970. We took as research source the processes initiated by CGI, Process number 50/1969-PR (about the donation of an area to Antônio Cid), Process number 219/1970 (deals with irregularities in the payment of pension and life insurance) and the Process number 232/1970 (denunciation to municipal management of Octacílio Mion), all occured in Cascavel, and interviews with one of the defendants. After analysis of the referred sources and comparison with specific bibliography, we observed the dispute of speeches/memories between the accusing commission and the defendants, verifying that in both sides there are unspoken facts, speech control, all intending self-benefit. Also, when analysing the conjuncture, we noticed the relationships of power constituted around the land possession, which were not restricted to a centralizer point, but to a power network linking the local and state political spheres, civil service and entrepreneurs related to land possession. We sought to present a contextualization of the Brazilian political scenery after the resignation of Jânio Quadros until the gestation of the civil-military coup d état of 1964, in order to understand the development of a moralizing speech of combat to the corruption developed by the militaries, used to justify the actions taken by their regulatory agencies, like the CGIs. Even though two General Comissions of Investigation (1964 and 1968) have been created, which were responsible for the withdrawal and punishment of politicians, civil servants, our research investigated the processes initiated by the second commission which, supported by AI-5, tended to investigate possible acts of illicit enrichment, acting, several times, through catalytic actions promoting the discipline of individuals, not only the investigated ones, but the population in general. Our local cut, the city of Cascavel, was presented from its formation in order to observe the connection between its development and the land exploration, since it became an element of dispute in the following decades. We could verify the development of a power network which spread to local and state public spheres, and to the private sphere, that to garantee and/or increase the amount of land possession, made use of public influence, physical violence and naivety of small landowners. Based on that we treated the CGI processes, which investigate the supposed acts of illicit enrichment in the local civil service, one being linked to the donation of land to Antônio Cid in the 1950s during the management of the former governor Moysés Lupion, of the non-payment of restitutions and pensions obstructed by the Registry Office of Cascavel-PR and, a last one, dealing with feasible corruption in the municipal administration in the managements of Octacilio Mion. This allowed us to observe the existence of corruption in the city of Cascavel, but both defendants and CGI made use of omission of facts, names and pages of the processes to minimize or guarantee sentences and avoid the inquiry of feasible corrupt people